1983
DOI: 10.1152/jappl.1983.55.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chest wall distortion on esophageal pressure

Abstract: The caudocephalad profile of esophageal pressure swings was studied in 10 preterm and 5 full-term infants, and the effect of chest wall distortion on esophageal pressure swings was analyzed in 12 preterm infants. Esophageal pressure was measured with a fluid-filled catheter, tidal volume with a pneumotachograph, mouth pressure with a face mask and pressure transducer, and rib cage and abdominal motion with magnetometers. In preterm infants the profile of esophageal pressure swings fell very steeply in the caud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(43 citation statements)
references
References 0 publications
1
40
1
1
Order By: Relevance
“…Our findings measuring esophageal pressure at two sites simultaneously in a group of preterm infants of similar birth weight and gestational age as in the study of Le Souef et al (10) do not support this interpretation. Nor is this interpretation supported by two recent studies (9,16).…”
Section: )contrasting
confidence: 94%
See 2 more Smart Citations
“…Our findings measuring esophageal pressure at two sites simultaneously in a group of preterm infants of similar birth weight and gestational age as in the study of Le Souef et al (10) do not support this interpretation. Nor is this interpretation supported by two recent studies (9,16).…”
Section: )contrasting
confidence: 94%
“…Although some investigators describe a good correlation between airway and esophageal pressure in neonates during airway occlusion (8,9), others have found this correlation highly variable (6,7). A differencebetween airway and esophageal pressure changes during occlusion has been observed especially in infants with lung disease (6) and chest wall distortion (10). It has been theorized that chest wall distortion leads to an unequal distribution of pleural pressure and that esophageal pressure, as a consequence, may not reflect mean pleural pressure changes (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our subjects this condition was found present at all levels of CPAP (see "Methods"), and so gives confidence in the method. Although cyclical changes in Pes may not accurately reflect cyclical changes of pleural pressure at all levels of the lung in premature infants (16), the present measurements are a good reflection of pleural pressure at the level of the heart.…”
Section: Discussionmentioning
confidence: 57%
“…The measurement of Pes in the presence of CWD has been described as unreliable, because it may reflect local pleural pressure changes rather than a mean pressure change (29). However, we reexamined this question recently and found that CWD does not affect Pes measurements adversely (30,31).…”
Section: Discussionmentioning
confidence: 79%